Direkam di sekolah, Sweet Seventeen, KTP-el ku Datang: Inovasi Pemerintah Kota Surakarta - Ria, Damai; Adnan, Muhammad (Journal of Politic and Government Studies, 2019)
E-KTP innovation is a method of improving optimal public services, noting that innovation can renew ineffective systems, especially in the field of civil registration. In optimal public service, community response is also important in the accountability of a public policy. This is stated in the example of the E-KTP innovation policy in Surakarta, namely "Recorded at school, Sweet Seventeen, KTP-el ku Datang" conducted by Dukcapil. This policy contains a program about E-KTP recording carried out in schools, the location of an individual who is 17 years old. The purpose of this innovation is to make it easier for individuals who have a status as a student to have complete state identity. The existence of innovation is also expected so that administrative management can be structured systematically in the field of civil registration, so that every statistic calculation of population can be calculated effectively and efficiently. This policy is expected to work better.Â